Pengembangan Soft Skills Peserta Didik melalui Integrasi Pendekatan Science, Technology, Engineering, Arts, and Mathematics (STEAM) dalam Pembelajaran Asam Basa - Mentari Reza Apriliana; Achmad Ridwan; Tritiyatma Hadinugrahaningsih; Yuli Rahmawati (LPPM Universitas Negeri Jakarta, 2018)
This research aims to develop students’ soft skills through integration STEAM approach in acid base learning. The research was conducted in year XI in the even semester of the academic year 2016/2017. This research employed qualitative research with data collection of interview, observation, and reflective journal. Learning activities were carried out by applying six stages of project-based learning, consisting of provide essential questions, design a plan for the project, create a project schedule, monitor students and project progress, assess or result the outcome, and evaluate the experience. Based on the results of the research can be concluded that integration of STEAM approach in project-based learning has developed students’ soft skills of cooperation, critical thinking, environmental awareness, responsibility, adaptability skills, and creative thinking. Keywords: STEAM approach, soft skills, acid-base learning